CoSe2 nanocrystals embedded into carbon support as coralline-like catalysts for hydrogen evolution reaction. (30th August 2019) - Zhao, Linghui; Jia, Jingchun; Chang, Ying; Jia, Meilin; Wen, Zhenhai
Abstract: It is vital to develop a high activity, stability and inexpensive hydrogen evolution reaction (HER) catalyst for electrochemical hydrogen evolution. A high-temperature reaction approach that is Co nanocrystals on carbon support (XC-72R) and selenylation to synthetize CoSe2 /C nanocrystals is used, and the effect of temperature on CoSe2 /C nanocrystals is studied. The morphology and catalytic properties of CoSe2 /C nanocrystals annealed at different temperatures are compared in 0.5 M H2 SO4 . The results indicated the coralline-like CoSe2 /C-650 nanocrystals have a high performance for HER with Tafel slopes of 45.73 mV·dec −1 and onset potential of −196 mV vs. RHE. The stability maintained for at least 40 h and the Faraday Efficiency (FE) of H2 is nearly 98%. The outstanding HER performance of CoSe2 /C-650 is due to its characteristic cora-like frame CoSe2 nanocrystals embedded into supernal conductive XC-72R, which not only offer affluent active reaction sites, but also boost the capacity of charge transportation in HER process. Graphical abstract: A reliable strategy is developed to fabricate coralline-like CoSe2 nanocrystals on carbon support (XC-72R); the effect of temperature on controlling CoSe2 nanocrystals is studied. The coral-like CoSe2 /C-650 shows high catalytic activity and stability, superior to that the obtained CoSe2 at other temperature, the onset potential for HER of −196 mV vs. RHE and Tafel slopes of 45.73 mV·dec −1 . The electrode also has excellent durability, catalytic activity being maintained for over 40 h and the FE was calculated of H2 is nearly 98%. The unique cora-like architecture constructed by CoSe2 nanocrystals embedded into highly conductive XC-72R, which can not only offer rich active reaction sites, but also boost the ability of charge transportation in HER process.Image 1 Highlights: A CoSe2 nanocrystals embedded into carbon support show a coralline-like structure. The effect of temperature on controlling CoSe2 nanocrystals. The CoSe2 /C-650 with a Tafel slopes of 45.73 mVdec −1 .